1990
DOI: 10.1117/12.962893
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Light Angle Reflectance Instrument I Polarized Incidence (POLAR:I)

Abstract: The light scattering properties of leaves are used as input data for models which mathematically describe the transport of photons within plant canopies. Polarization measurements may aid in the investigation of these properties. This paper describes an instrument for rapidly determining the bidirectional light scattering properties of leaves illuminated by linearly polarized light.Results for one species, magnolia, show large differences in the bidirectional light scattering properties depending whether or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…All our findings are in accord with the earlier results of Shul 'gin and Moldau (1964), Vanderbilt and Grant (1985a, b), Vanderbilt et al (1985a, b), Grant (1987), Grant et al (1987aGrant et al ( , b, 1993 and Sarto et al (1989), who measured the polarized, non-polarized and specular reflectance of leaves of many different plant species as functions of the leaf surface features in the visible and near-infrared parts of the spectrum by pointsource polarimetry. They found that in some viewing directions the surface reflection is so large that leaves appear white instead of green.…”
Section: Reflection-polarization Characteristics Of Plant Surfacessupporting
confidence: 93%
“…All our findings are in accord with the earlier results of Shul 'gin and Moldau (1964), Vanderbilt and Grant (1985a, b), Vanderbilt et al (1985a, b), Grant (1987), Grant et al (1987aGrant et al ( , b, 1993 and Sarto et al (1989), who measured the polarized, non-polarized and specular reflectance of leaves of many different plant species as functions of the leaf surface features in the visible and near-infrared parts of the spectrum by pointsource polarimetry. They found that in some viewing directions the surface reflection is so large that leaves appear white instead of green.…”
Section: Reflection-polarization Characteristics Of Plant Surfacessupporting
confidence: 93%
“…Sometimes however, it is just the opposite: the detectors are fixed and the light source is mounted on a rotation stage (Okayama, 1996). Finally, in other devices, all components are fixed (Sarto et al, 1989). In all reports, measurements are performed in the visible/near-infrared region, in one to several wavebands, and in polarized or non-polarized conditions, but very few of them combined both the spectral and directional dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of leaf directional properties is complex and needs sophisticated devices such as a gonio-reflectometer (e.g. Combes et al, 2007;Woolley, 1971), an imaging sphere (Sarto, Woldemar, & Vanderbilt, 1990), or a conoscope (Comar et al, 2012). Other existing systems could be used (Marschner, Westin, Lafortune, & Torrance, 2000), but no results have been reported in the literature for leaves.…”
Section: Introductionmentioning
confidence: 99%